In Coconut and Arecanut... Enhancing income through system approach and value-addition - Chowdappa, P; Jayasenkar, S (Indian Horticulture, 2019)
Plantation sector assumes a crucial role by supporting livelihood to millions of small and marginal holders in our country. Besides, this sector contributes towards employment generation on account of its labour intensity, facilitating inclusive development. Of late, most of the plantation crops are confronted with umpteen challenges that affect the profitability and sustainability as a whole. It is a challenging task to convert the production node into farming systems because the structural rigidity of most of the conventional cropping methods does not allow this. Adoption of any cropping system by farming community will ultimately be decided by its economic advantage. The interest for palm-based farming systems has stemmed from both technical and economic grounds. When we consider the monocropping of trees from the labour utilization point of view, we find that barring the establishment stage, labour absorption is low and seasonal, for the remaining life span. For the regions with surplus labour, this type of systems may not be desirable. Another economic disadvantage of monocropping is that the investment in establishing the crop till its bearing age becomes sizable, which a small holder may not be able to afford.